2008
DOI: 10.2527/jas.2007-0342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing fish oil in the drinking water of dairy cows on production performance and milk fatty acid composition1

Abstract: The objective of this study was to determine the effects of supplementing fish oil (FO) in the drinking water of dairy cows on production performance and milk fatty acid composition. Sixteen multiparous Holstein dairy cows (741 +/- 84 kg of BW; 60 +/- 2.3 d in milk, mean +/- SD) housed in a tie-stall facility were used in the study. The study was conducted as a completely randomized design with repeated measurements. The cows were blocked by days in milk and allocated to 1 of 2 treatments: 10 g of menhaden FO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
(46 reference statements)
3
14
1
Order By: Relevance
“…The mean BCFA levels reported in the present study fall within the range previously reported in studies that measured cow’s milk FA in response to various diets in small scale experimental studies [3-5, 8, 10]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The mean BCFA levels reported in the present study fall within the range previously reported in studies that measured cow’s milk FA in response to various diets in small scale experimental studies [3-5, 8, 10]. …”
Section: Resultssupporting
confidence: 88%
“…Both iso - and anteiso -13:0 BCFA in cow’s milk have been reported by some [3, 5, 8, 11] but not by others [4, 6, 26]. In the present study, retail milk samples were obtained from processing plants and represent pooled milk from many farms; use of specific feeds on some farms that may support small amounts of ruminal C13 BCFA could be diluted to below detection limits by the milk from other farms [10, 27].…”
Section: Resultsmentioning
confidence: 93%
“…Concentration of VA in milk fat followed the same pattern of temporal changes as cis ‐9 trans ‐11 CLA. FOM supplementation in TMR doses of cows resulted in a higher increase in the concentration of cis‐ 9, trans ‐12 CLA isomer (1.33%) in milk fat compared with FO supplementation in drinking water (0.88%) (Osborne et al., 2008). Our experiment as well as other studies (AbuGhazaleh et al., 2004; Castañeda‐Gutieérrez et al., 2007) demonstrated a significant increase in VA content in milk after FO supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This study contained 33% of herring‐sprat oil, which characterized high percentage of 40.43% of PUFA including 29.5% the omega‐3 family (n‐3), polyunsaturated fatty acids n‐3 such as EPA (8.19%) and DHA (13.83%). In other studies, mainly fish oil delivered from menhaden fish, which contained the lower DHA content (ranging 10.95–11.92 g/100 g fatty acids), was used (AbuGhazaleh et al., 2003; Osborne et al., 2008). In the beginning of the study, the content of DHA was below detection (<10 −3 ) in the milk fat of the control cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation